Midnight in Soap Lake : a novel [large type] - Sullivan, Matthew, 1970- (Thorndike Press large print high octane., 2025)
"Abigail has moved to Soap Lake, Washington to assist with her husband's research. Instead of craft beer and folksy neighbours, she finds a dry, desolate landscape around a town subsisting on its meagre crops. What's more, her husband has left her there alone for six months to go on a research trip. One day, across the hardpan desert, a boy runs out of the brush literally into Abigail's arms. He is catatonic, and his clothes are covered with blood. His mother, Esme, lies stabbed to death in a nearby car. Abigail is desperate to find answers, and as she digs, Esme's tragic life in is unearthed. Yet somehow, her search has caught the attention of something malevolent that lurks in Soap Lake's every shadow. What started as curiosity becomes a desperate compulsion, as Abigail is drawn into a complex web of conspiracies and violence, and learns that the smallest towns can hide the biggest secrets."--